Impact of the 2017 AAP clinical guideline on the prevalence of high blood pressure among adolescents in Lagos, Nigeria - Atoh, Ifeoma; Ezeogu, Joseph; Ekure, Ekanem; Omokhodion, Samuel Ilenre; Njokanma, Fidelis Olisamedua (Frontiers in Pediatrics, 2023)
Introduction: Adolescent high blood pressure (HBP); can lead to several end-organ complications if it tracks into adulthood. The 2017 AAP Guideline has lower blood pressure cut off points, and consequently leads to identification of more people with high blood pressure. This study evaluated the impact of the 2017 American Academy of Pediatrics (AAP) Guideline on the prevalence of high blood pressure among adolescents when compared with the 2004 Fourth Report. Methodology: A descriptive cross-sectional study was, conducted from August 2020 to December 2020. Selection of 1490 students, 10 to 19 years old, was by two-stage sampling technique. Socio-demographic information and relevant clinical data were obtained using a structured questionnaire. Blood pressure was measured according to standard protocol Categorical and numerical variables were summarized using frequency, percentages, mean and standard deviation. Chi-square and McNemar Bowker tests of symmetry were used to compare the blood pressure values of 2004 Fourth report and 2017 AAP Guideline. Results: Prevalence rates of High blood pressure, elevated blood pressure and hypertension among adolescents were 26.7%, 13.8% and 12.9% using the 2017 AAP Clinical Guideline; 14.5%, 6.1% and 8.4% using the 2004 Fourth Report. The degree of agreement between the 2004 and 2017 guidelines with respect to the classification of blood pressure was 84.8%. The Kappa statistic was 0.71 (CI: 0.67 to 0.75). The impact of this is a 12.2%, 7.7%, 4.5% increase in the prevalence of high blood pressure, elevated blood pressure and hypertension using the 2017 AAP Clinical Guideline. Conclusion: The 2017 AAP Clinical Guideline detects a greater proportion of high blood pressure among adolescents. The adoption of this new guideline in clinical practice and its use in the routine screening of high blood pressure among adolescents is recommended.